The Effect Of Educational Competitive Exercises With Aids To Develop The Motor Behavior Of The Accuracy Of The Skill Of Simple Attack In Volleyball For Juniors - Subhan Sakhi, Ali; Amer Fakher, Thamer; Bahjat Abbas, Aqeel (International Journal of Psychosocial Rehabilitation, 2020)
The research included an introduction to the research and its importance, as to keep pace with the development in the field of kinetic learning, researchers and specialists must find modern and innovative means to develop the technical level of players’ performance, and this is what the educational process witnessed to raise the levels of players and the requirements of the game to achieve the best results. In volleyball, their training is almost devoid of learning a skill that is very important in scoring decisive points, which is the skill of simple attack. Through this skill, the player can turn the result in his favor by deceiving the blocking wall and exploiting the existing spaces to drop the ball The importance of the research lies in developing the skill of the simple attack by preparing educational competitive exercises and reaching this skill to the best possible level. The researchers hypothesized that there are statistically significant differences between the results of the tribal and remote tests of motor behavior for the accuracy of the skill of simple attack in volleyball for the experimental and control groups. As for the fields of research, the sample consisted of young players of specialized schools and was divided into two groups, experimental and control, for each group (10) players with 24 educational units. The researcher’s work with the experimental group was limited to 35 d in the main part of the training unit time. The second chapter included the method used, where the researchers used the experimental method for the experimental and control groups with pre and post tests, due to its suitability to the nature of the study. While the third chapter contained a presentation, analysis, and discussion of the results obtained by researchers from the designed tests, and comparison was made between the pre- and post-results for both the experimental and control groups. After presenting, analyzing, and discussing the results of the research, the researchers reached the following conclusions: The competitive exercises and designed aids helped in developing the motor behavior and the accuracy of the simple attack skill of the young players in volleyball. As for the recommendations, the researchers recommended the use of educational competitive exercises and aids to develop motor behavior for the accuracy of the skill of simple attack in volleyball for young people.